Expansion of a SNaPshot assay to a 55‐SNP multiplex: Assay enhancements, validation, and power in forensic science. Issue 10 (9th March 2016) - Wang, Qian; Fu, Lihong; Zhang, Xiaojing; Dai, Xinyu; Bai, Mei; Fu, Guangping; Cong, Bin; Li, Shujin
Abstract : A previously developed multiplex assay with 44 individual identification SNPs was expanded to a 55plex assay. Fifty‐four highly informative SNPs and an amelogenin sex marker were amplified in one PCR reaction and then detected with two SNaPshot reactions using CE. PCR primers for four loci, 28 single‐base extension primers, and the reaction conditions were altered to improve the robustness of the method. A detailed approach for allele calling was developed to guide analysis of the electropherogram. One hundred and eighty unrelated individuals and 100 father‐child‐mother trios of the Han population in Hebei, China were analyzed. No mutation was found in the SNP loci. The combined mean match probability and cumulative probability of exclusion were 1.327 × 10 −22 and 0.999932, respectively. Analysis of the 54 SNPs and 26 STRs (included in the AmpFLSTR Identifiler and Investigator HDplex kits) showed no significant linkage disequilibriums. Our research shows that the expanded SNP multiplex assay is an easily performed and valuable method to supplement STR analysis.